Incidence of gross and microscopic carcinoma in specimens from patients with breast cancer after re-excision lumpectomy. - Gwin, J L (1993)
OBJECTIVE: The aims of this study were to quantify the amount of the residual carcinoma in re-excision lumpectomy specimens and retrospectively analyze the relationship between clinical parameters and the characteristics of the primary excision to these quantities of the residual tumor. SUMMARY BACKGROUND DATA: Because complete gross surgical excision of the primary tumor is important in minimizing local recurrence in women undergoing breast conservation therapy, re-excision of the initial biopsy site is commonly practiced when the initial primary tumor excision shows inadequate or undeterminable margins. Several studies have reported a significant proportion of re-excision specimens to contain residual tumor (32% to 63%), but to the authors' knowledge, none have quantified the amount of residual tumor. METHODS: The authors reviewed 192 re-excisions retrospectively to quantify the amount of residual carcinoma and correlate the quantities with the characteristics of the primary tumor resection. RESULTS: No tumor was found in 105 (54.7%) specimens, 46 (23.9%) had minimal microscopic disease, 23 (12.0%) had extensive microscopic disease, and 18 (9.4%) had gross residual cancer. Characteristics significantly associated with the quantity of residual disease included clinical tumor stage (T stage), pathologic T stage, and the margin status of the primary excision. The majority (62.1%) of re-excision specimens containing residual carcinoma had an invasive component. CONCLUSIONS: It was concluded that re-excision lumpectomy yields an important number of patients with residual carcinoma and that characteristics of both the primary tumor and primary excision significantly predict the quantity of residual cancer in the specimen. In addition, these results support the policy of performing re-excision for patients with inadequate or undeterminable margins for the primary excision.